2019
DOI: 10.1038/s41598-019-40347-6
|View full text |Cite
|
Sign up to set email alerts
|

Intensity of Nosema ceranae infection is associated with specific honey bee gut bacteria and weakly associated with gut microbiome structure

Abstract: The honey bee, Apis mellifera , pollinates a wide variety of essential crops in numerous ecosystems around the world but faces many modern challenges. Among these, the microsporidian pathogen Nosema ceranae is one of the primary detriments to honey bee health. Nosema infects the honey bee gut, which harbors a highly specific, coevolved microbiota heavily involved in bee immune function and nutrition. Here, we extend previous work investigatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
54
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 79 publications
(61 citation statements)
references
References 54 publications
5
54
0
1
Order By: Relevance
“…It has been suggested that the active microbiota differ in total abundance and species richness at different bee ages (Hroncova et al, 2015). Therefore, spore development of the infection caused by N. ceranae can be affected by this variation in the intestinal microbiota (Rubanov et al, 2019), because of competition for host resources. This variation in the relative abundance of certain bacterial taxa with a function in the nutrition and health of bees, is directly associated with differences in the landscape (Jones et al, 2018), and the succession of these communities appears to be related to the genetic diversity and age of honey bees (Anderson et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the active microbiota differ in total abundance and species richness at different bee ages (Hroncova et al, 2015). Therefore, spore development of the infection caused by N. ceranae can be affected by this variation in the intestinal microbiota (Rubanov et al, 2019), because of competition for host resources. This variation in the relative abundance of certain bacterial taxa with a function in the nutrition and health of bees, is directly associated with differences in the landscape (Jones et al, 2018), and the succession of these communities appears to be related to the genetic diversity and age of honey bees (Anderson et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The distinct gut microbiomes present in social bees are largely consistent worldwide (2428) and positively affect bee health via toxicant metabolism (29), immune system stimulation (30) and protection against pathogens (25,31,32). While the bacterial members of the microbiome remain generally consistent, stressors have been found to alter the microbial community, as found during times of inconsistent forage availability (33,34), antibiotic exposure (35), infection (36), and pesticide exposure (37). During times of host stress, the symbiotic community of bacteria within the gut can collapse, removing its positive effect on bee health and effectively causing dysbiosis of the gut microbiome.…”
Section: Introductionmentioning
confidence: 99%
“…Although previous studies with bumble bees have implicated Gilliamella‐ rich microbiota in resistance to C. bombi infection (Koch and Schmid‐Hempel, ; Mockler et al ., ), the Orbaceae clade is phenotypically diverse, varying in traits such as carbohydrate metabolism and resistance to antimicrobial peptides despite conserved 16S rRNA gene sequences (Engel et al ., ; Kwong et al ., ), and may harbour strains associated with both health and disease. For example, a cross‐colony survey correlated high levels of Gilliamella (‘Gamma‐1’) with honey bee colony collapse (Cox‐Foster et al ., ), intensity of infection with the honey bee‐infective microsporidian Nosema ceranae (Rubanov et al ., ), and general ‘dysbiosis’ associated with low adult bee mass, high mortality, the scab‐forming bacterium Frischella perrara , and Nosema infection (Maes et al ., ).…”
Section: Discussionmentioning
confidence: 99%